"Listen, Touch, and Move!": Integrasi TPR dan Sensory Play untuk Meningkatkan Bahasa Inggris Reseptif Anak Usia Dini - Nury Kurnia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Receptive language skills, which include listening skills, decoding linguistics and responding meaningfully to verbal instructions, are identified as an essential foundation and absolute prerequisite before children can enter the expressive language production phase. Conventional approaches that are too teacher-centered and emphasize memorization methods have proven to often fail. Through the Classroom Action Research (CAR) design of the Kemmis and McTaggart spiral model implemented in two cycles of action. Empirical data were collected through triangulation methods that included in-depth participatory observation, non-verbal performance tests, and documentation. The subjects of this study were 15 children in group B at Al Hidayah III Kindergarten, Gebang, Jember. The results of data analysis showed a very significant, consistent, and measurable increase in classical receptive language skills. The level of completeness of understanding English teaching increased from a baseline average of 41.75% in the pre-Cycle stage, increasing to 59% in Cycle I, and to 86% at the end of Cycle II. The findings of this study indicate that the TPR method integrated with Sensory Play media is not merely a substitution technique for vocabulary teaching, but rather a learning method that simultaneously stimulates children's cognitive functions, emotional abilities, fine motor coordination, and language literacy. This is highly recommended for adaptation, institutionalization, and widespread application in the development of Early Childhood Education (PAUD) curriculum to build a strong, interactive, meaningful foundation for foreign language/English mastery, and is relevant to the challenges of holistic education in the contemporary era.